Perancangan Lembar Kerja Siswa pada Modul Pembelajaran Mandiri IPA Biologi SMP Berbasis Edmodo untuk Siswa Terdampak Bencana - Rahmayunita, Desy; Sudargo, Fransiska; Syulasmi, Ammi (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
Natural disaster such as flood often hit Baleendah, district of Bandung. Flood impacts in environment damage and also in education. Students cannot go to school because of the access of the road, school and house blocked by flood. Therefore, alternative learning is needed through the use of teaching materials in the form of student worksheet based on Edmodo in providing services for students impacted by disaster. This study aims to produce Biology student worksheet in Junior High School self-directed learning products for students affected by disaster Edmodo-based. The research method used descriptive research using 4D development model (Define, Design, Develop and Disseminate). However, researcher only focus on the design stage.The respondents of this research are the students of grade VII and science teacher of SMPN 1 Baleendah. The instruments used include the assessment sheet of student worksheet development and student response questionnaire. Assessment is based on aspects of eligibility, readability and student responsiveness. The results showed that student worksheet developed based on the feasibility aspect previously considered by experts based on didactic requirements, construction requirements and technical requirements are categorized very well with the average percentage of 81.24%. Student response to student worksheet is very good, where student worksheet can help students in self-study. However, the independence of student learning is considered less, and still require direct assistance from the teacher. In addition, the availability of smartphones, signals, and quotas need to be considered in accessing this Edmodo-based student worksheet.